Campaign Against Poisoning - Abd Razak, Dzulkifli (1995)
The industrial revolution of the 19th century gives new meaning to what 'poisons' are. As the growth and expansion of the chemical industry reached its heights, the incidences of poisoning markedly increased, particularly at the early stages of its development. Currently, there are some 80,000 chemicals in use according to the International Register of Potentially Toxic Chemicals based in Geneva; and as many as three new chemicals entering the market daily. Not only are the industrial workers more exposed to toxic substances, other members of the public are also implicated as more and more of these substances find their way into the society at large. There are now substances ranging from pesticides to detergents, pharmaceuticals and cosmetics, a whole range food additives, preservatives, antioxidants and so on. Today there is no household, agricultural plantation and industrial firm that does not use any chemical substance, so much so it is difficult to imagine how modem living would proceed without them. There was even at one time a perfume named 'Poison' an epitomy perhaps of how close these chemicals are in 'brightening up' of daily lives.